Peranan Job Embeddedness dalam Memediasi Pengaruh Pemberdayaan Psikologis terhadap Komitmen Organisasi - M. Attakaatsur Akbar; Ririn Handayani; Fahmi Oemar (CV. ITTC INDONESIA, 2025)
This study was conducted at PT. Tri Erdnov Rezeki with the aim of testing the mediating role of job embeddedness on the influence of psychological empowerment on organizational commitment. The population of this study was employees of PT. Tri Erdnov Rezeki totaling 85 people. Based on this population size, the sampling method used in this study is the saturated sample method where the entire population is sampled. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that psychological empowerment has a significant positive effect on organizational commitment; psychological empowerment has a significant positive effect on job embeddedness; job embeddedness has a significant positive effect on organizational commitment; and job embeddedness mediates the effect of psychological empowerment on organizational commitment.